Development of Wearable Electromyogram for The Physical Fatigue Detection During Aerobic Activity - Zulkifli Ahmad (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe